TANTANGAN DAN KESULITAN SIBLING DARI INDIVIDU BERKEBUTUHAN KHUSUS - Nur, Haerani; Zainuddin, Kurniati (JURNAL SIPAKALEBBI, 2023)
Sibling is one of the important sources of support in families with individuals with special needs, but sometimes they may not be able to fulfill their roles effectively due to various challenges and difficulties they face. This study aims to explore the challenges and difficulties experienced by siblings of individuals with special needs. A search for research articles was conducted using keywords such as "sibling experience, sibling difficulties, sibling challenges of individuals with special needs." A total of 25 journal articles obtained from Google Scholar were systematically reviewed using the Meta-synthesis Qualitative Research method. Several themes have been identified to describe the challenges and difficulties faced by siblings. Feelings of loneliness, anxiety, and sadness, jealousy, guilt, and self-blame, feeling overwhelmed, and even tendencies toward depression are some of the emotional challenges experienced by siblings. Limited social interactions, tendencies to withdraw, and concerns about bullying are some of the social challenges experienced by siblings. Challenges for siblings are closely related to difficulties in accepting and understanding their sibling’s condition, the inability to balance their own needs and responsibilities towards their sibling, and difficulties in adapting to changes in their daily lives. The causes of these challenges and difficulties can stem from the condition of the sibling, parents, the sibling themselves, and the environment’s response to the presence of individuals with special needs. The results of this study are expected to provide a basis for formulating further research or intervention programs to optimize the role of siblings in supporting their siblings with special needs.